1995
DOI: 10.1248/bpb.18.850
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Anti-urease Action by the Anti-ulcer Drug Ecabet Sodium.

Abstract: To investigate the mechanism of the anti-urease action of ecabet sodium (ecabet) observed in Helicobacter pylori in vitro, the effects of ecabet on purified urease from jack bean were studied in comparison with the effects of the specific urease inhibitor benzohydroxamic acid (BHA). After incubation of the enzyme with the test drug for a period of time, urease activity was measured. Ecabet depressed the activity below pH 5, and the lower the pH, the greater the degree of depression. The degree of depression by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Recent studies have demonstrated that ecabet sodium has anti‐ H. pylori activity. In vitro studies have shown that ecabet sodium inhibits urease activity of H. pylori and adhesion to gastric epithelial cells 9 , . 10 , 24 In addition, ecabet sodium is reported to have suppressive activity on the growth of H. pylori in a dose‐dependent manner 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that ecabet sodium has anti‐ H. pylori activity. In vitro studies have shown that ecabet sodium inhibits urease activity of H. pylori and adhesion to gastric epithelial cells 9 , . 10 , 24 In addition, ecabet sodium is reported to have suppressive activity on the growth of H. pylori in a dose‐dependent manner 12 .…”
Section: Discussionmentioning
confidence: 99%
“… 7 Ecabet sodium, which is a widely used cytoprotective agent for the gastric mucosa, is reported not only to have anti‐pepsin activity, but also to inhibit urease activity and growth of H. pylori. 8 –12 Several studies have shown that the addition of ecabet sodium increases the eradication rate of proton pump inhibitor‐based dual therapy for H. pylori infection 13 –16 . To our knowledge, the efficacy and safety of ecabet sodium‐based triple therapy with two antimicrobial agents has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Urease is essential for H. pylori to live under acidic conditions 26 . Ecabet sodium irreversibly inhibits coarse urease derived from H. pylori at pH 5, which is the optimal pH for urease 27 –28 . Ecabet sodium also exhibited a dose‐dependent and rapid bactericidal effect against H. pylori in an acidic environment, although it had no effect on the viability of H. pylori in a neutral environment 29 .…”
Section: Discussionmentioning
confidence: 99%
“…tried to eradicate H. pylori, with disappointing results, with a long term assumption of probiotics shown to have a good inhibitory effect on H. pyori growth in vitro [134]. However, Ecabet sodium is an old antiulcer agent with demonstrated activity against H. pylori growth related to urease inhibition and reduction of the adhesion of bacteria on gastric mucosa [138][139][140][141]. It has been succesfully tested in H. pylori eradication, firstly in monkeys [142].…”
Section: Other Strategiesmentioning
confidence: 99%